The Design of the Role Model of Working Women (Occupational Health Perspective) - Utami, Tri Niswati; Nuraini, Nuraini (Universitas Teuku Umar, 2020)
The purpose of this research study is to find and explain the role models of working women. This type of qualitative research uses descriptive design. Secondary data sources obtained from the 2017 IDHS data, data on married women who work, and tertiary data sources that reference several previously research sources. Univariate data analysis to calculate the distribution of the prevalence of working women. Tertiary data were analyzed using the Invivo 12 application to build concepts or role models. The results showed that the prevalence of working women was 80.3% (246 people), not working 2.8% (9 people) and not working in the last 12 months by 16.7% (52 people). The role models of women working in the family, which are: family mediators, support for their husbands, sources of income, family care, and children's education. The women who work have responsibilities to the family, the same as women who do not work (housewives). We conclude that the prevalence of married women who work increases, influenced by family needs and social strata of society. The working women have a dual role. There are an advised to continue to carry out their duties and responsibilities towards the family.